2001
DOI: 10.1093/rheumatology/40.12.1398
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine and immunogenetic profiles in Japanese patients with adult Still's disease. Association with chronic articular disease

Abstract: The present study suggests that ASD with chronic articular disease has distinct clinical, cytokine and immunogenetic profiles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
98
1
6

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(109 citation statements)
references
References 19 publications
4
98
1
6
Order By: Relevance
“…In reports on both conditions, serum IL-6 levels have been correlated with specific markers of disease activity, including joint involvement, skin rash, pyrexia, CRP and ferritin levels, elevated liver enzymes, and leukocytosis [42][43][44][45][46][47]. Macrophages and endothelial cells are the main sources of IL-6, a cytokine that is responsible not only for the production of acute-phase proteins by hepatocytes, but also for hyperferritinemia, characterized by the uptake of free iron and ferritin synthesis [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…In reports on both conditions, serum IL-6 levels have been correlated with specific markers of disease activity, including joint involvement, skin rash, pyrexia, CRP and ferritin levels, elevated liver enzymes, and leukocytosis [42][43][44][45][46][47]. Macrophages and endothelial cells are the main sources of IL-6, a cytokine that is responsible not only for the production of acute-phase proteins by hepatocytes, but also for hyperferritinemia, characterized by the uptake of free iron and ferritin synthesis [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…3 Although its pathogenesis is still unclear, high serum levels of several cytokines such as IL-1b, IL-6, tumor necrosis factor (TNF)-a and interferon (IFN)-g have been suggested to play roles in the disease. 4,5 However, elevated levels of these cytokines are not specific for AOSD since they are often elevated in other systemic inflammatory diseases such as sepsis, rheumatoid arthritis (RA) and JRA. Recently, we reported that serum IL-18 levels were significantly elevated (more than 1000-fold) in AOSD patients compared with those in patients with other inflammatory disorders such as RA and JRA as well as healthy individuals.…”
Section: Introductionmentioning
confidence: 99%
“…[27] In another study on Japanese patients, DRB1*1501 (DR2) and DRB1*1201 (DR5) alleles were more frequent in chronic articular than in polycyclic systemic AOSD; whereas DQB1*0602 (DQ1) was observed in all types of AOSD. [28] Polymorphism in IL-1 and IL-18 genes was proposed by a few authors as a possible mechanism in pathogenesis of AOSD, but the former was not found to be associated with AOSD. Also, possession of the diplotype conÞ guration of S01/S01 was found to be a major genetic risk factor for susceptibility to AOSD.…”
Section: Pathogenesismentioning
confidence: 99%
“…Cagatay et al [84] Chen et al [82] Pouchot et al [62] Mert et al [20] Bambery et al [18] Singh et al [14] Mehrpoor et al [28] ferritin is glycosylated; while in inß ammatory diseases, it drops to 20%-50%; and in AOSD, less than 20%. [3,95] Recently, in some studies, it was shown that hyper-ferritinemia, which is correlated to histiocyte hyperactivity, can lead to an association of AOSD with MAS.…”
Section: Clinical Features (Number Of Patients)mentioning
confidence: 99%